Investment Expenditure Behavior of Remittance Receiving Households: An Analysis Using Reserve Bank of India Data - Basu, Bharati; Rajan, Irudaya (Migration Letters, 2018)
Although it is the world’s largest recipient of remittances, India lacks information about the investment behavior of its remittance receiving households. Using data from Reserve Bank of India and the Tobit analysis, this paper examines how remittances, different household and migrant characteristics have affected both the propensity to invest and the amount of investment by the remittance receiving households. The findings have significant implications for policy purposes. For example, government programs can create incentives for older migrants to have more remittance transfers. Remittance money used for children’s education could be matched to create robust flow of educational investments.